2017
DOI: 10.1038/cti.2017.34
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL‐17A by secukinumab shows no evidence of increased Mycobacterium tuberculosis infections

Abstract: Secukinumab, a fully human monoclonal antibody that selectively neutralizes interleukin-17A (IL-17A), has been shown to have significant efficacy in the treatment of moderate to severe psoriasis, psoriatic arthritis and ankylosing spondylitis. Blocking critical mediators of immunity may carry a risk of increased opportunistic infections. Here we present clinical and in vitro findings examining the effect of secukinumab on Mycobacterium tuberculosis infection. We re-assessed the effect of secukinumab on the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 66 publications
(282 reference statements)
4
65
0
2
Order By: Relevance
“…By blocking critical mediators of adaptive and innate immunity, biotherapeutics may carry a risk of increased opportunistic infections. IL‐17A has a role in immune defense in mucocutaneous barrier tissues and may play a role during Mycobacterium tuberculosis infection 19 …”
Section: Discussionmentioning
confidence: 99%
“…By blocking critical mediators of adaptive and innate immunity, biotherapeutics may carry a risk of increased opportunistic infections. IL‐17A has a role in immune defense in mucocutaneous barrier tissues and may play a role during Mycobacterium tuberculosis infection 19 …”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis of four clinical trials of ustekinumab revealed that the risk of TB with ustekinumab is lower than that observed with anti‐TNF‐α‐therapy . Additionally, Kammuller et al . reported that clinical investigations with secukinumab have shown no evidence of TB infection.…”
Section: Safety Concerns Specific For Each Biologicmentioning
confidence: 99%
“…A meta-analysis of four clinical trials of ustekinumab revealed that the risk of TB with ustekinumab is lower than that observed with anti-TNF-a-therapy. 21 Additionally, Kammuller et al 22 reported that clinical investigations with secukinumab have shown no evidence of TB infection. Although the risks of LTBI reactivation with IL-12/ 23p40 antibody and IL-17 inhibitors differ from those with TNFa inhibitors, established guidelines in the USA, 23 Europe 24 and Japan 25 recommend screening prior to initiation of any biologics for psoriasis.…”
Section: Tuberculosismentioning
confidence: 99%
“…However, members of the TFP felt that specific clinical considerations in the local context need to be acknowledged, such as higher exposure to tuberculosis. A recent review of pool safety data from trials involving secukinumab did not show an increased risk of tuberculosis infection . Alongside growing experience of the use of secukinumab in Singapore, having an additional first‐line option available is important.…”
Section: Resultsmentioning
confidence: 99%
“…A recent review of pool safety data from trials involving secukinumab did not show an increased risk of tuberculosis infection. 36 Alongside growing experience of the use of secukinumab in Singapore, having an additional first-line option available is…”
Section: If Bdmard Is Considered Either Tnfi or Il17i May Be Consimentioning
confidence: 99%